Reception traditions of Romanticism in the literary legacy of Karen Blixen - Капустян, Марія Григорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article is devoted to the study of interpretation of Karen Blixen in the Nordic scientific and critical discourse of the late XIX century - early XX century. The critics focused on the author’s manner of the creation of artistic images, her authentic simplicity and comprehensiveness of her individual style. The notion of interpretation was considered in the traditional sense and on the account of contemporary literary process, which includes leading literary critics of Scandinavian countries. Particular attention is paid to the writer’s translation into other languages (EasternSlavic,etc.).Romantic ideas and art techniques are creatively recycled by the writer and are subjected to reinterpretation. Pilosophical views of K.Blixen were considered and was found out that typological connection with the romantic writers at extraordinary heroes were allowed with the help of her characters.